The Rise and Fall of Civil Religion: Comparative Perspectives - Markoff, John (Sociological analysis, 1981)
This paper posits that one common source for diverse civil religious experiments is a “reaction to a problematic pluralism.” We seek to demonstrate this by focusing on two cases removed from each other in time and space: post-revolutionary France and contemporary Malaysia. They also differ sharply in the particular civil religious variant and mood adopted, which we illustrate in an initial, descriptive section on civic rituals and beliefs for our two core cases. After showing that French civil religion is participatory and ecstatic while Malaysia's is passive and controlled, we ask why modern civil religions are so visible at certain historical junctures. We locate the answer in particular, politically troublesome features of the formation of national states and view the roots of civil religion in a central state's assault on its citizens' parochial identities. It is when gaps are experienced between parochial identities and the claims of the state that civil religion is generated. Finally, after exploring three major variants of civil religion — their existence and viability for our two cases and selected others — we ask: why do modern civil religions fail?